Psychometric Properties of the Workforce Agility Scale - Viranda, Chintia; Safitri, Irma; Hidayat, Safrudin (Psychological Research on Urban Society, 2023)
Society 5.0 is a concept of society that must humanize humans with technology. If the industrial revolution 4.0 makes humans more modern because they have access to technology, then society 5.0 is a time where technology becomes part of humans. Industrial revolution 5.0 employees are more focused on being prepared to think critically, analytically and creatively to adapt in the future. Therefore, this research aims to test the construct validity of the workforce agility measurement tool. To test the psychometric characteristics of this research, researchers will use an item response theory approach with the Rasch model. In this research, data collection was carried out by distributing instruments or questionnaires to respondents using Likert. This research consisted of 182 respondents. The results of this study show that the validity of the items is quite good with a unidimensional value of 30.2%, there are 24 scale items that are identified as fit or according to the Rasch model reliability coefficient (item = 0.96, respondent = 0.88, Cronbach's alpha = 0.89). The analysis also shows that there are four gender bias items (male, female). From these results, this scale can be used to measure workforce agility of workers in companies or members of organizations.